High-density lipoprotein-cholesterol functionality and metabolic syndrome: Protocol for review and meta-analysis. Issue 24 (June 2018) - Roever, Leonardo; Resende, Elmiro Santos; Diniz, Angélica Lemos Debs; Penha-Silva, Nilson; O'Connell, João Lucas; Gomes, Paulo Fernando Silva; Zanetti, Hugo Ribeiro; Roerver-Borges, Anaisa Silva; Veloso, Fernando César; Souza, Fernanda Rodrigues de; Duarte, Poliana Rodrigues Alves; Fidale, Thiago Montes; et al.
Abstract: Introduction: The prevalence of metabolic syndrome (MetS) and MetS-related stroke is set to increase dramatically in coming decades. MetS is a complex disease that includes endothelial dysfunction, insulin resistance, diabetes, hypertension, ectopic obesity, and dyslipidaemia and an increased risk of cardiovascular events. One function of high-density lipoprotein (HDL) cholesterol (HDL-C) is the cholesterol-efflux pathway, which is the pathway where cholesterol is removed from macrophages within the arterial walls back into the bloodstream and out to the liver. As one of the key functions of HDL, their hypothesis was that if they could measure HDL-C-efflux capacity, they would have a better handle on the role of HDL in atherosclerosis. However, there are no systematic analyses or well-conducted meta-analyses to evaluate the relationship between HDL-C functionality and MetS. The aim of this study is to examine this association of HDL-C functionality with MetS in different ages and sex. Methods and analysis: The update systematic review and meta-analysis will be conducted using published studies that will be identified from electronic databases (i.e., PubMed, EMBASE, Web of Science, and Google Scholar). Studies that examined the association between HDL-C functionality and MetS; focused on cohort, case-control, and cross-sectional studies; were conducted among in adults aged 40 to 70 years; provided sufficient data for calculating odds ratio or relative risk with a 95% confidence interval; were published as original articles written in English or other languages; and have been published until January 2018 will be included. Study selection, data collection, quality assessment, and statistical syntheses will be conducted based on discussions among investigators. Ethics and dissemination: Ethics approval was not required for this study because it was based on published studies. The results and findings of this study will be submitted and published in a scientific peer-reviewed journal. Trial registration number: PROSPERO (CRD42018083465).